1970
DOI: 10.1071/ar9700807
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnant mare serum gonadotrophin and human chorionic gonadotrophin on ovulation and on fertility in the ewe

Abstract: An experiment involving 300 cyclic Merino ewes and designed to study the effects of pregnant mare serum gonadotrophin (PMSG) and human chorionic gonadotrophin (HCG) on ovulation and subsequent fertility is described. PMSG (750 i.u.) was given on the 12th day of the oestrous cycle and HCG (400 and 800 i.u.) was injected intravenously within 3 hr of the onset of oestrus. PMSG induced multiple ovulation and hastened the time of ovulation in relation to the onset of oestrus by 2-3 hr, but did not enhance the preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

1975
1975
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Shorter intervals in the eCGtreated groups are attributed to the action of eCG on follicular growth by mediating faster pituitary endocrine responses and estradiol secretion. Treatment with eCG has been shown to advance the intervals to estrus and ovulation in sheep [9,22,23] . These effects are consistent with gonadotropic action of eCG in sheep [23,24] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter intervals in the eCGtreated groups are attributed to the action of eCG on follicular growth by mediating faster pituitary endocrine responses and estradiol secretion. Treatment with eCG has been shown to advance the intervals to estrus and ovulation in sheep [9,22,23] . These effects are consistent with gonadotropic action of eCG in sheep [23,24] .…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with eCG has been shown to advance the intervals to estrus and ovulation in sheep [9,22,23] . These effects are consistent with gonadotropic action of eCG in sheep [23,24] . Progesterone profile prior to and following sponge removal: Initial plasma P 4 concentrations on days -12, -4 and on day 0 were basal among groups and averaged 0.1 ± 0.02 ng mL -1 , indicating absence of cyclicity and seasonal anestrus.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it may be a reflection of earlier ovulation in ewes with higher ovulatory responses to the gonadotrophin. Time of ovulation in relation to progestagen withdrawal has been shown previously to be advanced by treatment with PMSG (Killeen & Moore, 1970) and FSH (Evans & Armstrong, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of follicles which rupture has been found to increase when HCG is given within 3 hr after the onset of oestrus in cyclic sheep stimulated with 750 i.u. PMSG in the follicular phase of the cycle (Killeen & Moore, 1970 (Rippel, Moyer, Johnson & Mauer, 1974). These authors concluded that the degree of follicular maturation accounted for these differences because very little follicular growth was evident during anoestrus.…”
mentioning
confidence: 86%